1981
DOI: 10.1055/s-2007-1019160
|View full text |Cite
|
Sign up to set email alerts
|

T4-T3Shift during the Postprandial Period After Glucose Load in Obese Children before and after Hypocaloric Diet - One Factor for Postprandial Thermogenesis?

Abstract: Reactions of the plasma concentrations of the thermogenetically active thyroid hormones T 3 and T 4 were studied in overweight children during the postprandial period after glucose load before and after feeding a hypocaloric diet.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1982
1982
2018
2018

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
(10 reference statements)
0
3
0
Order By: Relevance
“…Previously, oral and intravenous glucose loads induced T4 reduction and slightly increased T3-levels postprandially in overweight children. 54 Conversely, a hypocaloric intervention (600-1000 kcal per day) for 21 days reduced T3 while increas- ing T4 concentrations after an oral glucose load. 54 In the current study we showed that a WWB meal challenge containing 50 g available CHO, irrespective of BPB consumption, could potentially affect postprandial thyroid hormones in healthy subjects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, oral and intravenous glucose loads induced T4 reduction and slightly increased T3-levels postprandially in overweight children. 54 Conversely, a hypocaloric intervention (600-1000 kcal per day) for 21 days reduced T3 while increas- ing T4 concentrations after an oral glucose load. 54 In the current study we showed that a WWB meal challenge containing 50 g available CHO, irrespective of BPB consumption, could potentially affect postprandial thyroid hormones in healthy subjects.…”
Section: Discussionmentioning
confidence: 99%
“…54 Conversely, a hypocaloric intervention (600-1000 kcal per day) for 21 days reduced T3 while increas- ing T4 concentrations after an oral glucose load. 54 In the current study we showed that a WWB meal challenge containing 50 g available CHO, irrespective of BPB consumption, could potentially affect postprandial thyroid hormones in healthy subjects. While the effect of BPB on T3 was observed as a time effect, the multivariate analysis showed that subjects with BPB (indicated as a blue dot; Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Such exces-sive wastage is usually attributed to the brown adipose tissue in rodents; this phenomenon is called dietary-or meal-induced thermogenesis (Rothwell & Stock, 1979). In humans, the causal mechanism for the phenomenon is not as well understood, although changes in the efficiency of thyroid hormone may play a role (Hesse, Spahn, & Pienert, 1981).…”
Section: The Problem Of Satietymentioning
confidence: 99%